The effect of Si content on structure and mechanical features of silicon-containing calcium-phosphate-based films deposited by RF-magnetron sputtering on titanium substrate treated by pulsed electron beam. Issue 1 (October 2015) - Surmeneva, M; Tyurin, A; Mukhametkaliyev, T; Teresov, A; Koval, A; Pirozhkova, T; Shuvarin, I; Chudinova, E; Surmenev, R
Abstract: Silicon-containing calcium phosphate (Si-CaP) coatings were fabricated by radio frequency (rf) magnetron sputtering using the targets prepared from hydroxyapatite (HA) powder with different silicon content. A powder of Si-HA (Ca10 (PO4 )6-x (SiO4 )x (OH)2-x, x=0.5 and 1.72) was prepared by mechanochemical activation and then used as a precursor-powder to prepare a target for sputtering. The titanium substrate was acid etched and treated with pulsed electron beam with an energy density of 15 J/cm 2 . The average crystallite size as determined by XRD was 28 nm for the coatings obtained using the target prepared from the Si-HA powder (x=0.5), whereas Si-CaP (Si-HA powder x=1.72) films showed an amorphous structure. The nanohardness and the Young's modulus of the Si-CaP coating (x=0.5) deposited on titanium treated by pulsed electron beam are enhanced to 4.5 and 113 GPa compared to titanium substrate. Increase of Si content resulted in a dramatic decrease of the nanohardness and Young's modulus of Si-CaP films. However, Si-CaP coatings with the highest Si content revealed significantly lower values of elastic modulus, but slightly higher values of H/E and H 3 /E 2 than did the non-coated specimens. Rf-magnetron sputtering allowed us to produce Si- CaP coatings with higher nanohardness and lower elastic modulus compared to titanium substrate.